Optimization of Business Management in Improving the Welfare of Palm Farmers - Ameliany, Nanda; Sufi, Sufi; Ritonga, Nursakinah; Iryani, Lisa; Meliza, Richa; Rosida, Erni (Neraca Keuangan : Jurnal Ilmiah Akuntansi dan Keuangan, 2025)
This research aims to determine the management strategies implemented by Alue Luehop village and the obstacles experienced by Alue Leuhop village. research focus: 1) What are the management strategies at benchmarks 1 to 4. (2) Obstacles to business management strategies in increasing income at benchmarks 1 to 4. This research uses qualitative methods. There were 14 informants for this research, 12 purposive and 2 accidental. The data analysis technique used in this research uses data reduction, data presentation and drawing conclusions. Based on the results of the research and discussions that have been studied, the researcher concludes that the management strategy in Alue Leuhop village is a lack of understanding in carrying out management strategies which can result in a lack of fertilization, cleaning will cause the palm fruit to die or the palm fruit to decrease. Obstacles that occur in the management strategy include the track fruit which every year experiences track fruit for 3-4 months during the track fruit period, pests and also animals which can cause the palm fruit to die or wilt.